Generation of a BEST1 Pr-EGFP reporter human embryonic stem cell line via CRISPR/Cas9 editing - Shuaiyan Lu; Ming Chen; Xiaoyu Liu; Jiahang Li; Hui Liu; Shasha Li (Stem Cell Research)
The retinal pigment epithelium (RPE) cell, located between the neural retina and choriocapillaris, is vital for retinal maintenance and photoreceptor function. Human embryonic stem cells (hESCs) provide a limitless source of RPE cells for transplantation. Using CRISPR/Cas9, we inserted a fusion of the BEST1 promoter (an RPE-specific marker) and the EGFP gene into the AAVS1 locus to track differentiation in hESC-induced RPE (hESC-iRPE). The resulting gene-edited line, WAe009-A-2 M, maintained a normal karyotype, expressed pluripotency markers, and demonstrated differentiation potential, making it invaluable for RPE development and therapeutic research.